Anteseden Burnout pada Perawat Muslim saat Pandemi Covid-19: Telaah Literatur - Randika Shafly Fawwaz; Mirwan Surya Perdhana (Jurnal Ilmiah Ekonomi Islam, 2022)
The global pandemic of coronavirus disease 2019 (COVID-19) has drastically changed the way we live and work. In the midst of a protracted pandemic, the exhaustion of frontline healthcare professionals is a significant concern. Thus those working on the front lines of health care are at increased risk of infection and are asked to work in ways that are unclear, foreign or contrary to the normative path of their role. Among health workers, nurses have experienced higher burnout. Nurse fatigue occurs when excessive workloads are exacerbated by deep-rooted systemic problems such as irregular working hours, overtime, rotating shifts and staff shortages. This discrepancy with the resulting between expectations and reality as a profession, increases burnout. This study aims to provide a comprehensive and comprehensive exploration of the effect of burnout on nurses during the Covid-19 pandemic. The article that will be used in this research is an article that discusses burnout that occurs in nurses during the Covid-19 pandemic and uses 30 articles from 2020 to 2021.